Investigation on machinability of Al 2024& 7.5% Si3N4 metal matrix composite with PMEDM using Taguchi based GRA. (2021) - Rajavel, R.; Selvarajan, L.; Rajkumar, G.; Raja, R.; Rakshna, A.
Abstract: In this analysis, an investigation and testing work were carried out on the PEDM of Al 2024& 7.5% Si3 N4 Metal Matrix material composite performed with copper electrodes. Taguchi design and Grey relational analysis has been analyzed the experiments using MINITAB-17. The effects of the input process parameters viz. pulse on time (Ton ), pulse off-time (Toff ) & current and concentration of the aluminium powder in IPOL dielectric (C) were it effects on material removal rate (MRR), surface roughness (Ra ) and it was optimized for high MRR, low Ra and machining timing. From the analysis it is observed that Seventh specimen was considered to be Maximum Grey Relation grade under the conditions of A3 B1 C3 . This shows that the use of aluminium powder was found to be more suitable for improving the surface characteristics. As result shows that pulse-on time is the dominating factor comparative with others factors for Al2024 metal matrix. The estimated grey relational grade was increased from 0.681 to 0.723, which is the largest value obtained in all the experimental results in Grey Relational Analysis.